Myocardial Scar Detected by Cardiovascular Magnetic Resonance in a Competitive Bodybuilder With Longstanding Abuse of Anabolic Steroids - Baumann, Stefan (Asian J Sports Med, 2014)
INTRODUCTION: The self-administration intake of anabolic-androgenic steroids (AAS) is a widespread practice in competitive bodybuilders. Structural changes within the myocardium following AAS abuse including hypertrophy, restricted diastolic function as well as systolic dysfunction and impaired ventricular inflow have been reported. CASE PRESENTATION: We present the case of a 39-year-old bodybuilder with a more than 20-year history of anabolic-androgenic steroids (AAS) abuse presenting with increasing exertional dyspnoea and fatigue. Diagnostic work-up of the patient’s current symptoms included a cine cardiovascular magnetic resonance (CMR). Using a T1-weighted inversion-recovery sequence 10 minutes after application of 0.1 mmol/kg gadolinium with diethylenetriaminepentaacetic acid (gadolinium DTPA), patchy midwall enhancement in the septal and posterolateral region of the left ventricle was demonstrated. This enhancement pattern is different from the enhancement pattern found in patients with ischemic heart disease. CONCLUSIONS: The present case illustrates for the first time, by CMR, myocardial scarring with severe left ventricular hypertrophy in a patient with normal coronary arteries after long lasting abuse of AAS. With that finding we could demonstrate a link between AAS abuse and the occurrence of myocardial scarring in humans. This finding may help raise awareness of the consequences of AAS use.